"Pattern as reference": windows of trainability among adolescents - Norjali Wazir, Mohd Rozilee Wazir; Ramli, Alif Syamim Syazwan (Pitesti University publishing house, 2021)
Introduction: Physical trainability among adolescents is crucial to optimize training and obtain best adaptations for physical performance, which is also related to anthropometric growth profiles. Problem Statement: Previous studies have shown different growth profiles inter-countries, hence this warrants more investigations on potential variance in patterns of windows of trainability. Purpose: The purpose of this study is to investigate how physical growth can be associated with and affected physical trainability among adolescents for training optimization purpose. Materials & Methods: A total of 800 students (400 boys and 400 girls) aged between 9 to 16 years participated in this study using fishbowl technique. Participants' weight and weight were measured and six physical fitness tests consisted of push-up (PU), bleep test (BLEEP), sit and reach (SnR), standing broad jump (SBJ), 30-meter sprint (SPRINT), and 10-meter shuttle run (SR) were tested. Results & Discussions: The results showed that peak growth seemed to occur around 13 and 14 years old for male students whereas 10 and 11 years old for female students. Peak of physical performance for male and female students aged 9 to 16 years old occurred before, during and after peak growth period, with both male and female students demonstrating their certain patterns. In overall, there was a significant relationship between physical growth and physical performance between 9 to 16 years old for both male and female students. Conclusions: The patterns obtained from this study could be used as a reference and guideline to plan physical training for adolescents, especially during PHV period where the peak of physical performance occurs for the windows of trainability for the long-term development.